Impaired cognitive control in patients with brain tumors. (3rd May 2022) - Tarantino, Vincenza; Visalli, Antonino; Facchini, Silvia; Rossato, Chiara; Bertoldo, Alessandra; Silvestri, Erica; Cecchin, Diego; Capizzi, Mariagrazia; Anglani, Mariagiulia; Baro, Valentina; Denaro, Luca; Della Puppa, Alessandro; et al.
Abstract: Though the assessment of cognitive functions is proven to be a reliable prognostic indicator in patients with brain tumors, some of these functions, such as cognitive control, are still rarely investigated. The objective of this study was to examine proactive and reactive control functions in patients with focal brain tumors and to identify lesioned brain areas more at "risk" for developing impairment of these functions. To this end, a group of twenty-two patients, candidate to surgery, were tested with an AX-CPT task and a Stroop task, along with a clinical neuropsychological assessment, and their performance was compared to that of a well-matched healthy control group. Although overall accuracy and response times were similar for patients and control groups, the patient group failed more on the BX trials of the AX-CPT task and on the incongruent trials of the Stroop task, specifically. Behavioral results were associated with the damaged brain areas, mostly distributed in right frontal regions, by means of a lesion-symptom mapping multivariate approach. This analysis showed that a white matter cluster in the right prefrontal area was associated with lower d' -context values on the AX-CPT, which reflected the fact that these patients rely more on later information (reactive processes) to respond to unexpected and conflicting stimuli, than on earlier contextual cues (proactive processes). Taken together, these results suggest that patients with brain tumors present an imbalance between proactive and reactive control strategies in high interfering conditions, in association with right prefrontal white matter lesions. Highlights: Brain tumor patients show a shift toward the use of reactive control processes. Right prefrontal lesions are associated with higher reliance on reactive control. White matter prefrontal cortex plays a role in cognitive control functions.